Effect of Tofu Fermented by Rhizopus sp. on Lowering Blood Glucose Level in White Rats (Rattus norvegicus) - Melati, Eldaa Putik Bunga; Wiboworini, Budiyanti; Subariyanti, Briandani (Nexus Kedokteran Translasional, 2017)
Introductions : Controlling of blood glucose would be an important prevention to prevent many complications of DM. Consuming fiber is one way to maintain blood glucose in normal level. These amount of fiber could be obtained in tofu fermented by Rhizopus sp. This research aimed to know the effect of tofu fermented by Rhizopus sp. in controlling blood glucose level of diabetic induced white rats (Rattus norvegicus). Methods : This research was a laboratoric-experimental study. The subjects were Rattus norvegicus grouped randomly. The total 30 Rattus norvegicus were injected by Alloxan 15mg/ 100 gram BW, then randomly allocated into 5 group, positive control group (glibenclamide 0,05 mg/100 gram BW/day), negative control group (aquadest), and treatment groups with different doses of fermented tofu (0,025 gram/100 gram BW/day; 0,050 gram/100 gram BW/day; 0,100 gram/100 gram BW/day). The research design was Pretest and Posttest Control Group Design. The fasting blood glucose were measured before Alloxan injection (day-2), after Alloxan injection (day-5), and after the treatments (day-19). Result : ANOVA showed that there was a significant decrease of blood glucose level in all treatment groups and positive control (p = 0,001). Post Hoc Test showed that there was significant difference between all treatment groups and positive control group compared to negative control group (p = 0,001). Conclusion : Tofu fermented by Rhizopus sp. was able to decrease blood glucose level in diabetic induced white rats (Rattus norvegicus). Keyword : Tofu fermented by Rhizopus sp, blood glucose level, white rats, Alloxan, glibenclamide